Organic Anion Transporter 5 (Oat5) Urinary Excretion Is a Specific Biomarker of Kidney Injury: Evaluation of Urinary Excretion of Exosomal Oat5 after N-Acetylcysteine Prevention of Cisplatin Induced Nephrotoxicity - Bulacio, Romina Paula (2015)
Cisplatin is a commonly used chemotherapeutic agent. Its main side-effect is nephrotoxicity. It was reported that the organic anion transporter 5 (Oat5) urinary excretion is elevated, implying renal perturbation, when no modifications of traditional markers of renal damage are still observed in cisplatin-induced acute kidney injury (AKI). It was also demonstrated that Oat5 is excreted in urine by the exosomal pathway. This study was designated to demonstrate the specific response of the urinary excretion of exosomal Oat5 to kidney injury independently of other cisplatin toxic effects, in order to strengthen Oat5 urinary levels as a specific biomarker of AKI. To accomplish that aim, we evaluated if urinary excretion of exosomal Oat5 returns to its basal levels when cisplatin renal damage is prevented by the coadministration of the renoprotective compound N-acetylcysteine. Four days after cisplatin administration, AKI was induced in cisplatin-treated male Wistar rats (Cis group), as it was corroborated by increased urea and creatinine plasma levels. Tubular damage was also observed. In cotreated animals (Cis + NAC group), plasma urea and creatinine concentrations tended to return to their basal values, and tubular damage was improved. Urinary excretion of exosomal Oat5 was notably increased in the Cis group, but when renal injury was ameliorated by N-acetylcysteine coadministration, that increase was undetected. So, in this work we observed that urinary excretion of exosomal Oat5 was only increased if renal insult is produced, demonstrating its specificity as a renal injury biomarker.